Analisis Anggaran Belanja Untuk Menilai Kinerja Dinas Energi dan Sumber Daya Mineral Provinsi Jawa Tengah - Hera Purwaningsih; Nibras Anny Khabibah (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
This study aims to analyze the performance of the Department of Energy and Mineral Resources of Central Java Province with reference to the budget. The method used in this research is qualitative which is processed using descriptive analysis. The data used are secondary data originating from the Budget Realization Report of the Department of Energy and Mineral Resources of Central Java Province for the period 2015 - 2018. The results show that: (1) Expenditure variance shows that budget savings have been made; (2) The compatibility ratio shows that the agency still prioritizes operating expenditures over capital expenditures; (3) Official financial performance is efficient and effective. Overall the performance of the Department of Energy and Mineral Resources of Central Java Province has been good.